Arms control and proliferation challenges to the reset policy - Blank, Stephen 1950- (Strategic Studies Institute monograph, 2011)
The current U.S. reset policy with Russia involves efforts to blaze a path of mutual cooperation on arms control and proliferation. In arms control, we see determined administration attempts to promote greater nuclear reductions in the direction of nuclear zero, including reductions in tactical nuclear weapons. This necessarily leads Moscow to raise issues of missile defense in Europe that it vehemently opposes. This monograph analyzes Russia's position on these arms control issues and examines the chances for the United States to achieve its arms control goals in the foreseeable future. It also looks at the Russian position with regard to the main nonproliferation issues of Iran and North Korea, what the implications of these positions are for the achievement of U.S. policy goals, and what the United States might do with regard to Russia to advance those goals in a dynamic international environment